Efficacy and safety of tranexamic acid in cervical spine surgery: a systematic review and meta-analysis - Luo, Hua; Yang, Yu; Wang, Zhitao; Ma, Lingping; Xie, Chengxin (Frontiers in Neurology, 2024)
Background: Tranexamic acid (TXA) is an antifibrinolytic drug associated with reduced blood loss in a range of surgical specialties. This meta-analysis aimed to compare the efficacy and safety of TXA in cervical surgery, focusing on its effects on intraoperative blood loss and related outcomes.We searched the PubMed, EMBASE, Medline, and Cochrane Library databases to identify all literature related to topical and intravenous TXA used in cervical spinal surgery. Eight trials met the inclusion criteria. Intraoperative blood loss, postoperative drainage volume, total blood loss, postoperative hematological variables, and complications were analyzed.Results: Eight trials met the inclusion criteria. The pooled results showed that intraoperative blood loss, total blood loss, and postoperative drainage volume were significantly higher lower in the TXA group than in the control group. The hemoglobin and hematocritconcentration on postoperative day 1 was significantly higher in the TXA group than in the control group. There was no significant difference in complications between the two groups.The available evidence indicates that TXA effectively reduces blood loss in cervical spinal surgery while maintaining a favorable safety profile, without increasing associated risks.The current evidence suggests that TXA significantly reduces blood loss in cervical surgery but has a good safety profile and does not increase the associated risks.